Introduction to the Buddhist Tantric Systems: Translated from: Mkhas Grub Rje’s "Rgyud sde spyihi rnam par gz’ag pa rgyas par brjod" with original text and annotation - Muppathinchira, T (Journal of Dharma, 1984)
Lessing & A. Wayman Introduction to the Buddhist Tantric Systems (Translated from: Mkhas Grub Rje’s "Rgyud sde spyihi rnam par gz’ag pa rgyas par brjod" with original text and annotation). Delhi: Motilal Banarsidass, 1978 (2nd ed.), 352pp.